MENGOMUNIKASIKAN KETELADANAN PANJI: Apresiator Kompleks dalam Budaya Etnik, Era Digital, Regulasi Kebudayaan - supriyanto, henricus (LPPM Universitas PGRI Adi Buana Surabaya, 2018)
The current proposed discussion is related to the complexity that is analyzed based on the stage of thinking.This happens because the current turn of the era which 'back and forth' turns out into a cultural cross. Not monitoredin detail, followed by a changing educational system, and not necessarily in tune with the needs and expectations ofgenerations of